Ants visible from space influence soil propertes and vegetaton in steppe rangelands of Iran - Ghobadi, M.; Agosti, D.; Mahdavi, M.; Jouri, M.; Majer, Jonathan (California State University Chico, 2016)
Messor nests in Iranian steppe rangelands can be so large that they are visible from space. When compared with reference soils, nest soil is higher in nutrients and lower in pH. Ant nests also homogenise the nutrients throughout the upper soil profile, although this effect diminished when nests are abandoned. The denuded circles around nests are surrounded by rings of vegetaton that differ in species compositon from that of the surrounding vegetaton, while abandoned nests are colonized by a different range of plant species. Data on the density and abundance of Messor cf. intermedius nests indicate that the soil in less than 1% of the area is impacted, although the cumulatve effect of so many nests influences the plant species and vegetaton structure of the region. The data indicate the importance of these ants in altering soil chemical compositon and plant diversity, which could have flow-on effects to the diversity of animals.